2017
DOI: 10.1111/ijfs.13582
|View full text |Cite
|
Sign up to set email alerts
|

Gluten‐free muffins: effects of sugar reduction and health benefit information on consumer liking, emotion, and purchase intent

Abstract: SummaryAvailability of reduced sugar gluten-free (GF) muffins remains commercially limited. In this study, selected physical properties, consumer perception and effects of health benefit information (HBI) were investigated for three GF muffins made with different amounts of sucrose (0%, 50%, 100%), with stevia used as a sucrose replacement. Sucrose reduction by 50%, unlike 100% with stevia, did not significantly decrease consumer acceptability (colour, odour, taste, sweetness, moistness, softness, stickiness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Making consumers aware of potential product benefits by providing a health claim can have a positive effect on acceptability, purchase intent (PI), and emotions associated with products such as grass‐fed beef steaks (Carabante et al., ) and gluten‐free muffins (Wardy et al., ). Recent research suggests that concurrently evaluating food‐elicited emotions with sensory liking improves prediction of consumer food choice (Gutjar et al., ; Jiang, King, & Prinyawiwatkul, ).…”
Section: Introductionmentioning
confidence: 99%
“…Making consumers aware of potential product benefits by providing a health claim can have a positive effect on acceptability, purchase intent (PI), and emotions associated with products such as grass‐fed beef steaks (Carabante et al., ) and gluten‐free muffins (Wardy et al., ). Recent research suggests that concurrently evaluating food‐elicited emotions with sensory liking improves prediction of consumer food choice (Gutjar et al., ; Jiang, King, & Prinyawiwatkul, ).…”
Section: Introductionmentioning
confidence: 99%
“…Maga (1974) discussed that salty foods were available in various colours, but no particular colour could be related to a salty taste. Some recent studies have documented the relevance between food-elicited emotion and characteristics of some products such as chicken egg (Wardy et al, 2015), sponge cake (Poonnakasem et al, 2016), iced tea (Wardy et al, 2018) and glutenfree muffins (Wardy et al, 2017b). Food colour is often used by consumers to inspect foods and decide on consumption or purchase intent.…”
Section: Introductionmentioning
confidence: 99%
“…A group of Thai consumers ( n = 110: 43.6% males and 56.4% females) who regularly purchased and used chili powder were asked to select all relevant terms as evoked by chili powder using check‐all‐that‐apply (CATA) on a printed paper questionnaire. Selection criteria from previous studies required at least 20% frequency responses (King & Meiselman, ; Poonnakasem, Pujols, Chaiwanichsiri, Laohasongkram, & Prinyawiwatkul, ; Sukkwai et al., ; Wardy et al., ), whereas others suggested at least 10% frequency responses (Bhumiratana et al., ; Tepsongkroh et al., ). For this study, terms with at least 14% frequency responses were considered in order to include as many terms as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Although hedonic scores are one of the criteria to guide food product development for many years, sensory liking is no longer an efficient sole parameter to predict food choice in real life environments, whereas emotion responses have successfully differentiated equally liked products (Jiang, King, & Prinyawiwatkul, ). Recent studies have observed the relationship between sensory characteristics and emotion of food products such as coffee (Bhumiratana, Adhikari, & Chambers, ), mayonnaise‐based dipping sauces (Sukkwai et al., ; Sukkwai, Chonpracha, Kijroongrojana, & Prinyawiwatkul, ), gluten‐free muffin (Wardy et al., ), and peanut products (Pujols, Ardoin, Chaiya, Tuuri, & Prinyawiwatkul, ; Sukkhown, Pirak, Chonpracha, Ardoin, & Prinyawiwatkul, ). They found that differences in visual cues of the products affected consumer perception, liking, emotions, and PI.…”
Section: Introductionmentioning
confidence: 99%